2020
DOI: 10.1037/emo0000596
|View full text |Cite
|
Sign up to set email alerts
|

On the automaticity of attentional orienting to threatening stimuli.

Abstract: Attention is biased toward stimuli that have been associated with aversive outcomes in the past. This bias has previously been interpreted as reflecting automatic orienting toward threat signals. However, in many prior studies, either the threatening stimulus provided valuable predictive information, signaling the possibility of an otherwise unavoidable punishment and thereby allowing participants to brace themselves, or the aversive event could be avoided with fast and accurate task performance. Under these c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 57 publications
(51 citation statements)
references
References 26 publications
1
47
3
Order By: Relevance
“…Our findings raise a broader question concerning the diversity of mechanisms by which learning history shapes attentional selection. For example, aversive conditioning is also known to bias attention to punishment-predictive stimuli (e.g., Anderson & Britton, 2019;Schmidt, Belopolsky & Theeuwes, 2015;Wang, Yu, & Zhou, 2013). It is unclear to what degree attentional biases driven by aversive conditioning are similar to and distinguishable from attentional biases driven by reward history and outcome-independent selection history.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings raise a broader question concerning the diversity of mechanisms by which learning history shapes attentional selection. For example, aversive conditioning is also known to bias attention to punishment-predictive stimuli (e.g., Anderson & Britton, 2019;Schmidt, Belopolsky & Theeuwes, 2015;Wang, Yu, & Zhou, 2013). It is unclear to what degree attentional biases driven by aversive conditioning are similar to and distinguishable from attentional biases driven by reward history and outcome-independent selection history.…”
Section: Discussionmentioning
confidence: 99%
“…Two runs of reward training were completed before each block of the test phase to mitigate possible extinction effects between the two blocks. Before entering the scanner, participants underwent a shock calibration procedure to achieve a level of shock that is "unpleasant, but not painful" (Anderson and Britton, 2019c;Kim and Anderson, 2019c) and were then disconnected from the shock device. Participants were reconnected to the shock device before beginning the test phase of the threat block and were immediately disconnected from the device after completion of the threat block.…”
Section: Task Proceduresmentioning
confidence: 99%
“…Attention can be voluntarily directed to objects (Duncan and Humphreys, 1989;Corbetta and Shulman, 2002) and spatial locations (Posner, 1980;Abrams et al, 2010). In addition, attention can be biased to prioritize the processing of features that are aligned with task goals (Wolfe et al, 1989;Folk et al, 1992), but also involuntarily captured by physically salient stimuli (Theeuwes, 1992) as well as stimuli previously associated with valent outcomes including punishment (Schmidt et al, 2015;Nissens et al, 2017;Anderson and Britton, 2019c) and reward (Hickey et al, 2010;Anderson et al, 2011;Anderson, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The attention task subsequently presents only the neutral stimuli to examine whether the learned associations with emotional content capture attention. In healthy individuals, studies have shown that associative learning of stable relations between a neutral stimulus (e.g., a shape or color) and aversive events (Anderson & Britton, 2019; Koster, Crombez, van Damme, Verschuere, & De Houwer, 2004; Schmidt, Belopolsky, & Theeuwes, 2015) or reward (Chelazzi, Perlato, Santandrea, & Della Libera, 2013; Hickey & van Zoest, 2013) involuntarily guides attention selection toward matching stimuli. For example, one study showed that task-irrelevant stimuli that were previously associated with reward, involuntarily capture attention and disrupt visual search for a salient target (Anderson, Laurent, & Yantis, 2011).…”
Section: Mechanisms Of Attention and Memory Interactions In Depressionmentioning
confidence: 99%